Secondary Metabolites Diversity of Aspergillus unguis and Their Bioactivities: A Potential Target to Be Explored - Levy Tenório Sousa Domingos; Raquel dos Santos Martins; Leonardo Melo de Lima; Angela Michelato Ghizelini; Antonio Ferreira-Pereira; Fernando Cotinguiba (Biomolecules, 2022)
Aspergillus unguis belongs to the Aspergillus section Nidulantes. This species is found in soils and organisms from marine environments, such as jellyfishes and sponges. The first chemical study reported in the literature dates from 1970, with depsidones nidulin (1), nornidulin (2), and unguinol (3) being the first isolated compounds. Fifty-two years since this first study, the isolation and characterization of ninety-seven (97) compounds have been reported. These compounds are from different classes, such as depsides, depsidones, phthalides, cyclopeptides, indanones, diarylethers, pyrones, benzoic acid derivatives, orcinol/orsenillate derivatives, and sesterpenoids. In terms of biological activities, the first studies on isolated compounds from A. unguis came only in the 1990s. Considering the tendency for antiparasitic and antibiotics to become ineffective against resistant microorganisms and larvae, A. unguis compounds have also been extensively investigated and some compounds are considered very promising. In addition to these larvicidal and antimicrobial activities, these compounds also show activity against cancer cell lines, animal growth promotion, antimalarial and antioxidant activities. Despite the diversity of these compounds and reported biological activities, A. unguis remains an interesting target for studies on metabolic induction to produce new compounds, the determination of new biological activities, medicinal chemistry, structural modification, biotechnological approaches, and molecular modeling, which have yet to be extensively explored.